2020
DOI: 10.1002/jssc.202000125
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of boronate‐functionalized surface molecularly imprinted polymer microspheres with polydopamine coating for specific recognition and separation of glycoside template

Abstract: A facile strategy based on the boronate affinity and polydopamine coating was proposed for the preparation of surface molecularly imprinted polymer microspheres using naringin as the glycoside template. The poly(methacrylic acid-co-methyl methacrylate-co-ethyleneglycol dimethacrylate) microspheres were firstly synthesized as inner cores by suspension polymerization method, and then functionalized with 3-aminophenylboronic acid. The imprinted shell layer was obtained by selfpolymerization of dopamine on the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…To the best of our knowledge, there are very few examples of glycans and glycoconjugates used as templates for catecholamine-based molecular imprinting in the literature, and only referred to the use of PDA. [37][38][39] Such paucity of experimental studies, despite the large literature on polydopamine, somehow suggested to test the more hydrophilic polynorepinephrine for sugar imprinting. [22][23][24] Accordingly, our preliminary studies employed mimetic and natural Tn antigens (1 and 2 respectively, see Figure 1) as templates for MIPs, and Tn_mime [37]BSA as a model of multivalent glycoprotein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there are very few examples of glycans and glycoconjugates used as templates for catecholamine-based molecular imprinting in the literature, and only referred to the use of PDA. [37][38][39] Such paucity of experimental studies, despite the large literature on polydopamine, somehow suggested to test the more hydrophilic polynorepinephrine for sugar imprinting. [22][23][24] Accordingly, our preliminary studies employed mimetic and natural Tn antigens (1 and 2 respectively, see Figure 1) as templates for MIPs, and Tn_mime [37]BSA as a model of multivalent glycoprotein.…”
Section: Resultsmentioning
confidence: 99%
“…The soundness of 1 to mimic the TnThr determinant, prompted us to synthesize 1 ‐imprinted polymers. To the best of our knowledge, there are very few examples of glycans and glycoconjugates used as templates for catecholamine‐based molecular imprinting in the literature, and only referred to the use of PDA [37–39] . Such paucity of experimental studies, despite the large literature on polydopamine, somehow suggested to test the more hydrophilic polynorepinephrine for sugar imprinting [22–24] .…”
Section: Resultsmentioning
confidence: 99%
“…Naringin and hesperidin are both flavanones. Successful preparation of MIPs of naringin [ 54 , 55 ] and hesperidin [ 56 ] has been reported. To selectively separate naringin from Citri Grandis, Pan et al [ 55 ] prepared MIP microspheres using surface imprinting, the IF of the MIP microspheres was 2.89.…”
Section: Methods For Preparing Mips Of Target Flavonoidsmentioning
confidence: 99%
“…Successful preparation of MIPs of naringin [ 54 , 55 ] and hesperidin [ 56 ] has been reported. To selectively separate naringin from Citri Grandis, Pan et al [ 55 ] prepared MIP microspheres using surface imprinting, the IF of the MIP microspheres was 2.89. Using the MIPs as molecular recognition elements, a fluorescent magnetic MIP sensor towards naringin was successfully constructed [ 54 ].…”
Section: Methods For Preparing Mips Of Target Flavonoidsmentioning
confidence: 99%
“…In addition, the MIP‐grafted or coated silica spheres were also reported for pretreatment of pharmaceutical samples [143–148]. As an example, Zhu et al.…”
Section: Applications Of Molecularly Imprinted Polymer‐based Spe To Rmentioning
confidence: 99%